E-Magazine Berbasis Aplikasi Book Creator Terhadap Kemampuan Literasi Digital Siswa - Oksaprillia, Wanda (FACTUM: Jurnal Sejarah dan Pendidikan Sejarah, 2024)
Digital literacy skills significantly assist students in searching for and utilizing historical information on the internet. The research objective is to identify the differences in the influence of implementing an e-magazine based on the Book Creator application on students' digital literacy abilities in history learning between the experimental and control groups. This study employs a quasi-experimental method in the form of Nonequivalent Group Pretest Posttest Design. The testing results indicate a difference in the influence on students' digital literacy abilities in history learning between the experimental and control groups. The results also demonstrate that the majority of students' digital literacy abilities in history learning fall into the high category. This article is expected to provide benefits to relevant parties including teachers, schools, and future researchers.